Fissureless Non-arterial Dissection Videothoracoscopic Lobectomy for Lower Lobes - Kara, Murat; Duman, Salih; Kolbas, Ilker; Sarigul, Arda; Cuhatutar, Seyhmus; Ozkan, Berker (The Thoracic and Cardiovascular Surgeon, 2025)
Two primary techniques, namely, the conventional transfissural and the fissureless approaches, have been defined for videothoracoscopic lobectomy. We hypothesized that a videothoracoscopic fissureless, non-arterial dissection (NAD) technique—using new generation staplers—for lower lobe resections may reduce operative time and lower the intra- and postoperative complication rates.We had 69 consecutive patients assigned to a fissureless NAD or a conventional lobectomy for lower lobes. In the fissureless NAD technique, the pulmonary artery, together with the adjacent lung parenchyma along the fissure line, was divided as the last anatomical structure using staplers with tri-height cartridges. We analyzed the feasibility and safety of the fissureless NAD technique.A total of 29 (42%) patients underwent NAD lobectomy. The mean operative time was significantly shorter in the NAD group (p = 0.003). No patient had intraoperative complication, and three (10.3%) patients (p = 0.212) had postoperative complication in the NAD group. The mean time of chest tube removal (p = 0.031) and the length of hospital stay (p = 0.008) were significantly shorter in the NAD group.The fissureless NAD videothoracoscopic lobectomy is a safe and feasible technique for lower lobectomies. This technique significantly reduces the operative time with potential benefit of earlier patient discharge.
Keywords: thoracoscopy/VATS; lung cancer treatment (surgery medical); surgery/incisions